Estudio comparativo de 2 férulas oclusales; seccionada y total en pacientes bruxistas, empleando electromiografía en músculos temporal y masetero - Muñoz Hernández, Gisela Herendira (Universidad Michoacana de San Nicolás de Hidalgo, 2020)
Using occlusal splints is a treatment for different types of Temporomandibular disorders (TMD). Sectioned occlusal splint is an alternative for the reduction or correction of bruxism and TMD before or after an orthodontic treatment, rehabilitation or some definitive treatment. Objective: To evaluate the effectiveness of 2 occlusal splints, sectioned and total, in bruxist patients, by using electromyography in masseter and temporal muscles. Material and methods: 20 patients aged between 20-40 years (13 women and 7 men) were treated. Randomly distributed in 2 groups: n1 = 10 (total occlusal splint), n2 = 10 (sectioned occlusal splint). An initial electromyography was recorded for each patient, they were checked every 8 days after the splints were placed during the first month, in the second and third months they were followed up every 15 days until they fulfilled 4 months of treatment. T Student was used for the statistical analysis at α / 2 = 0.05. Results: The total occlusal splint showed a lower rate of decrease in muscle amplitude. In the masseter muscles the initial amplitude was 300.6 ± 87μV and the final was 250.4 ± 89μV. In relation to the temporal muscles, the initial amplitude was 248.1 ± 87.1μV and the final 208 ± 51.9μV, p˂0.05. The sectioned occlusal splint showed a higher rate of decrease in muscle amplitude. In the masseter muscles the initial amplitude was 295.8 ± 109.3μV and the final amplitude was 227 ± 65μV. In relation to the temporal muscles, the initial amplitude was 223.2 ± 59.2μV and the final 191.8 ± 35.9μV, p˂0.05. The statistical difference of the amplitude in the masseter muscles results in the 68.6 ± 62.7μV sectional occlusal splint and the 50.2 ± 129.5μV p˂0.05 full occlusal splint. The statistical difference in the amplitude in the temporal muscles results in the sectional occlusal splint 40.1 ± 31.1μV and in the total occlusal splint 31.4 ± 95.1μV p˂0.05.

El uso de las férulas oclusales, son un tratamiento para diferentes tipos de TTM. La férula oclusal seccionada es una alternativa para la disminución o corrección de bruxismo y /o TTM antes o en su defecto después de un tratamiento de ortodoncia, rehabilitación o algún tratamiento definitivo. Objetivo: Evaluar la efectividad de 2 férulas oclusales; seccionada y total, en pacientes bruxistas, empleando electromiografía en músculos maseteros y temporales. Material y métodos: Se trataron 20 pacientes con edades entre 20-40 años (13 mujeres y 7 hombres). Distribuidos aleatoriamente en 2 grupos: n1=10 (férula oclusal total), n2=10 (férula oclusal seccionada). Se registró una electromiografía inicial a cada paciente, se revisaron cada 8 días después de la colocación de las férulas durante el primer mes, en el segundo y tercer mes se dio seguimiento cada 15 días hasta cumplir 4 meses de tratamiento. Se utilizó t Student para el análisis estadístico a α/2=0.05. Resultados: La férula oclusal total presentó menor índice de disminución en amplitud muscular. En los músculos maseteros la amplitud inicial fue de 300.6±87μV y la amplitud final fue de 250.4±89μV. En relación a los músculos temporales, la amplitud inicial fue 248.1±87.1μV y la final 208±51.9μV, p>0.05. La férula oclusal seccionada presentó mayor índice de disminución de amplitud muscular. En los músculos maseteros la amplitud inicial fue de 295.8±109.3μV y la amplitud final fue de 227±65μV. En relación a los músculos temporales, la amplitud inicial fue 223.2±59.2μV y la final 191.8±35.9μV, p˂0.05. La diferencia estadística de la amplitud en los músculos maseteros da como resultado en la férula oclusal seccionada 68.6±62.7μV y en la férula oclusal total 50.2±129.5μV p˂0.05.
Facultad de Odontología. Especialidad en Ortodoncia
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4619; info:eu-repo/classification/cti/3; FO-E-2020-0109; Férulas oclusales; Corrección; Bruxismo